Motor Task Processing After Constraint-Induced Movement Therapy in Children With Cerebral Palsy: A Case Series - Karen P.Y. Liu (Shahid Beheshti University of Medical Sciences, 2020)
Constraint-induced movement therapy (CIMT) has shown positive results in children with hemiplegic cerebral palsy (CP). However, studies on neural basis of such functional gains are limited. This study reports the event-related potential (ERP) changes in two children with hemiplegic CP after receiving CIMT for three weeks. Both cases were nine years old, had a diagnosis of left hemiplegic CP, had normal intelligence, and were able to extend the wrist at least 20° and the metacarpophalangeal joint at least 10° from full flexion. Before and after the three-week intervention, the children participated in ERP sessions with a choice reaction task to capture the changes in neural mechanism after intervention. Both children exhibited improvement in reaction time (RT) in both hand tasks after the intervention. The improvement was larger in the affected hand than the unaffected hand. Improved accuracy rate (AC) and shortened P300 latencies in the affected hand were also demonstrated in both cases. Topographical maps showed that in centro-parietal regions, patterns shifted from central and left-lateralized to more central and right-lateralized. CMIT was a useful method in improving upper limb function in our cases.